Habilidad metalingüística en inglés como L2 en estudiantes universitarios mexicanos - Maya-Ruiz, Selene (Colombian Applied Linguistics Journal, 2024)
The problem with grammaticality judgment tests in the field of L2 acquisition lies in the fact that language users make intuitive judgments about the accuracy of the form and grammar of individual, decontextualized L2 sentences. This article replicates an empirical study using an untimed grammaticality judgment test conducted through PsychoPy software, assessing the metalinguistic abilities of 13 university students in distinguishing between grammatically correct and incorrect L2 constructions. Participants evaluated 68 structures considered universally difficult for L2 learners to acquire (Ellis, 2005). Results varied based on participants’ metalinguistic abilities, the type of error (morphological or syntactic), and the complexity of structures. Analysis revealed that grammatical judgments depend less on participants' overall linguistic competence in English as an L2 and more on their ability to reflect on language forms and meanings. The study concludes that participants more easily detect morphological than syntactic errors when processing individual, decontextualized L2 sentences, highlighting the non-linear nature of language acquisition.